A Case of Incomplete Removal of Horseshoe Kidney by Laparoscopic Nephrectomy in an Adult Leading to Urinary Leak: An Eye Opener. (2nd May 2019) - Venkat Ramanan, S.; Velmurugan, P.; Bhaskar Prakash, A. R.; Arora, Anuj; Karri, LeelaKrishna
Abstract : Horseshoe kidney is a common congenital fusion anomaly of the kidneys. It poses a challenge to surgeon because of its very variable anatomy in terms of location and lie, fusion, pelvicalyceal system, and the renal vessels. Here we describe a case of laparoscopic nephrectomy in a horseshoe kidney complicated by incomplete removal because of not realizing the lower and medial extent of pelvicalyceal system across midline to the contralateral side leading to persistent urine leak. The relevant anatomy and the necessary precautions to prevent such complication have been discussed.